PENGEMBANGAN TEKNOLOGI VIRTUAL REALITY GUNA MENINGKATKAN HASIL BELAJAR MAHASISWA DI ERA COVID-19 - Sartika Anori; Putra Jaya (Jaringan Sistem Informasi Robotik-JSR, 2021)
The purpose of this study was to develop VR technology in learning in order to improve student learning outcomes in the Department of Electronic Engineering Education, Padang State University. The development carried out is to develop VR technology in the learning module in the Electronic Components course in order to improve student learning outcomes. The development method used is the 4D development method which consists of four steps including Define, Design, Develop and Disseminate. The results of this study indicate that virtual reality technology which was developed in the form of a learning module for the Electronic Components course is valid, practical and effective to improve student learning outcomes of the Department of Electronic Engineering Education, State University of PadangKeywords: Learning Outcomes, Virtual Reality